Exploring the Nexus of English language Learning and Technology: A Comprehensive Study on Augmented Reality Applications in Academic Settings - Rizkina, Putri Amalia; Nabilla, Zelitta Marsha (UM Purwokerto Press, 2025)
Particularly at the higher levels of education, online learning is quickly growing throughout the 4.0 educational landscape. The incredible progress of technology has revolutionized education when paired with suitable pedagogy. This integration has opened up numerous possibilities for improving teaching quality using available technology. One of the newest technologies to aid in making learning dynamic and interesting is augmented reality. The widespread use of mobile devices worldwide is correlated with the widespread use of augmented reality. The article examines the dynamic interaction of learning English and augmented reality. Thus, this research presents the pedagogical potentials of mobile augmented reality by reviewing many works of literature in the field. After listing the empirical research on AR taken from ProQuest, Elsivier, Eric, Researchgate, DOAJ and national journals, this review discusses its advantages and disadvantages, especially with regard to English as a foreign language, and its practical applications which can be used for developing Augmented Reality materials. Further research also needs to investigate diverse mobile AR apps with QR code for more engaging virtual online courses.